Superfluorescence in metal halide perovskites - Tang, Yue (2024)
Superfluorescence (SF) is a unique quantum optical phenomenon where an ensemble of atoms or molecules exhibit coherent emission of an intense burst of light of high directionality, with temporal coherence. SF exhibits ultrafast optical characteristics and has been considerably explored in diverse inorganic and hybrid semiconductor materials at cryogenic temperatures, including inorganic and hybrid metal halide perovskites. Notably, SF has been reported in different perovskites’ nanocrystal superlattices, alongside two examples in thin films, impressively achieving SF at room temperature. The density of quantum emitters, excited state characteristics, interaction strengths, and temperature all affect the SF threshold. Although significant progress is reported in the observance of SF phenomena, a full interpretation of the relationship between the factors that determine the SF threshold and the intrinsic material properties remains unclear. This review addresses the current state-of-the-art observations of SF in perovskite systems, such as nanocrystal superlattices and thin films, elucidating the optical properties, ultrafast dynamics, and the proposed mechanisms for room-temperature SF. The review concludes with a discussion on the existing challenges, unresolved questions, and future perspectives for advancing perovskite SF research.